The United Nations Humans Rights Commission and the Search for Measures of Implementation - Quentin-Baxter, R Q (Victoria University of Wellington Law Review, 1999)
While the Universal Declaration of Human Rights claims to represent the basis of the law of nations and humanity, the message has not yet made much stir outside the small world of scholarship. It was frequently said that the era of international legislation must be followed by a period of concentration upon measures of implementation, and the Human Rights Commission has already turned its attention to that task. This paper traces the Commission's efforts and makes an assessment of their prospects of fruition, concluding that national sovereignty remains a significant obstacle.